Analysis of metabolic liver function and MR-morphological cholestatic parameters after SBRT of liver metastases - Dreher, Constantin; Wojtal, Paulina; Johann, Maren; Bicu, Alicia Simone; Kästner, Lena; Weiß, Christel; Hetjens, Svetlana; Tavakoli, Andrej; Nörenberg, Dominik; Blanck, Oliver; Oppitz, Hans; Bürgy, Daniel; et al. (Radiation oncology, 2025)
This study examined the longitudinal changes in metabolic liver function and MR-morphological dilatation of intrahepatic bile ducts in patients with stereotactic body radiation therapy (SBRT) for liver metastases.
Online veröffenticht: 13. Oktober 2025
Gesehen am 08.01.2026